SURGICAL TREATMENT OF OBSTRUCTIVE SLEEP APNEA - CASE REPORT - Olja Tanellari; Edlira Baruti; Carmen Savin; Victor Costan; Daniel Olteanu; Ramona Feier; Irina Zetu (Romanian Society of Oral Rehabilitation, 2020)
Obstructive sleep apnea (OSA) is characterized by repetitive episodes of nocturnal breathing interruption due to partial or complete upper airway collapse, mainly the oropharyngeal tract. OSA is known to cause symptoms, such as excessive daytime somnolence, and is associated with cardiovascular morbidity and mortality. Different treatment options are: continuous positive airway pressure (CPAP), nasal CPAP (nCPAP), mandibular advancement devices, and surgery. The purpose of this article was to describe the successful case of a severe OSA case treated by surgical and orthodontic approach.